2018
DOI: 10.4103/jhrs.jhrs_136_17
|View full text |Cite
|
Sign up to set email alerts
|

Equivalency of in vitro fertilization success rates in elective single blastocyst transfer and elective double blastocyst transfer: An example of equivalence methodology in clinical reproductive health

Abstract: Context:When comparing success rates between treatments, it is more appropriate to structure analyses in terms of equivalence rather than traditional analyses that assess differences. Unfortunately, no studies of elective single blastocyst transfer (eSBT) have been conducted in this manner.Aims:The objective of this study was to assess clinical equivalence of in vitro fertilization success rates among patients undergoing eSBT.Settings and Design:A historical prospective study was conducted at a private fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For example, double blastocyst transfer was associated with a nearly 60-fold increase in the probability of gemellary pregnancy (OR:59.933, 95% CI [27.298–131.58]) and a 3.84-fold increase in the incidence of preterm birth (OR:3.840, 95% CI [2.272–6.489]) compared to single blastocyst transfer. Jacobs, Klonoff-Cohen & Garzo (2018) found that single blastocyst transfer has a clinical pregnancy rate similar to double blastocyst transfer. It is well known that premature infants, especially low birth weight infants, have immature organ development.…”
Section: Discussionmentioning
confidence: 94%
“…For example, double blastocyst transfer was associated with a nearly 60-fold increase in the probability of gemellary pregnancy (OR:59.933, 95% CI [27.298–131.58]) and a 3.84-fold increase in the incidence of preterm birth (OR:3.840, 95% CI [2.272–6.489]) compared to single blastocyst transfer. Jacobs, Klonoff-Cohen & Garzo (2018) found that single blastocyst transfer has a clinical pregnancy rate similar to double blastocyst transfer. It is well known that premature infants, especially low birth weight infants, have immature organ development.…”
Section: Discussionmentioning
confidence: 94%
“…These factors also increase the risk of neonatal mortality and chronic diseases in adulthood, thus placing a heavy burden on the national health care system and the families involved ( 15 ). It has been argued that the high rate of multiple pregnancy and the additional complications associated with DBT outweigh the high live birth rate associated with DBT ( 16 ). The goal of ART is to achieve a full-term, singleton, healthy live birth, and the number of embryos transferred is a controllable factor that relates to the overall treatment outcome, maternal-fetal safety, and post-pregnancy health.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to cleavage-stage embryos, extending embryo culture to the blastocyst stage allowed for better evaluation of the implantation potential, yielding a higher IR [2][3][4]. Previous studies have posited that elective single blastocyst transfer could yield comparable clinical pregnancy rates (CPR) for patients with a good prognosis [1,5,6]. Although live birth rate (LBR) equivalence was not demonstrated, it was thought the additional complications associated with multiple gestations outweighed the potentially higher LBR [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have posited that elective single blastocyst transfer could yield comparable clinical pregnancy rates (CPR) for patients with a good prognosis [1,5,6]. Although live birth rate (LBR) equivalence was not demonstrated, it was thought the additional complications associated with multiple gestations outweighed the potentially higher LBR [5]. Additionally, frozen-thawed single blastocyst transfers have been found to result in enhanced CPR relative to fresh single blastocyst transfers in ovulatory women with a good prognosis [6].…”
Section: Introductionmentioning
confidence: 99%